Research on the evolutionary game of government and enterprises in carbon emission reduction under multi-market coordinated trading - Guo, Wei; Meng, Tao; Piao, Zheyong; Chen, Yian; Liu, Hao; Xu, Daming; Meng, Fanyan; Wang, Xin; Han, Jieping; Yan, Jing; Yang, Xiaolong; Li, Jiaqi; et al. (Frontiers in Sustainable Energy Policy, 2024)
The three primary markets for carbon emission reduction trading are green certificate, green power, and carbon emission right markets. This paper suggests utilizing game theory to analyze the behaviors of government and enterprises in multi-market synergistic trading. The main participants in the game are the government, electricity consuming enterprises, traditional power generators, and new energy power generators. The game model will be simulated using system dynamics, and recommendations and measures will be proposed.The findings indicate that: (1) the government's ultimate strategy is to "act" when the losses resulting from government inaction exceed the gains from government action. (2) Behavioural evolution is consistent when market participants refrain from adjusting their cost inputs in response to fluctuations in market prices. (3) The market price is not as high as possible, but too high a price inhibits emission reduction. The behavioral evolution of carbon emission reduction in multiple markets is revealed in this study, which is of great importance in the promotion of carbon emission reduction.